Y=-x³+3x²+9x-29
y`=-3x²+6x+9=-3(x²-2x-3)=0
x1+x2=2 U x1*x2=-3
x1=-1∉[1;4]
x2=3∈[1;4]
y(1)=-1+3+9-29=-18 наим
y(3)=-27+27+27-29=-2 наиб
y(4)=-64+48+36-29=-7
3x(0,6x-2)-9(0,2x-3)=3
1,8x²-6x-1,8x+27=3
1,8x²-6x-1,8x+27-3=0
1,8x²-7,8x+24=0
D=(-7,8)²-4*1,8*24=60,84-172,8=-111,96
x<0,корней нет
Ответ: 62+(28-19-9)-44 =62+28-19-9-44=62-44=18;
86-37-(53-24-15)=86-37-53+24+15=35;
77-58+(34-34)-26=77-58+34-34-26=77-58-26=-7;
50-(26-26)+(18+22)=50+18+22=50+40=90.
Пошаговое объяснение:
1) 49:7 = 7(кг) - вмещается в одну корзину
2) 7 - 2 = 5(кг) - вмещается в одно ведро
3) 45 : 5 = 9 ведер - нужно, чтобы вместить 45 кг яблок